Cell-penetrating peptide-bismuth bicycles - Voss, Saan; Adair, Liam D.; Achazi, Katharina; Kim, Heeyoung; Bergemann, Silke; Bartenschlager, Ralf; New, Elizabeth J.; Rademann, Jörg; Nitsche, Christoph (Angewandte Chemie. International edition, 2024)
Cell-penetrating peptides (CPPs) play a significant role in the delivery of cargos into human cells. We report the first CPPs based on peptide-bismuth bicycles, which can be readily obtained from commercially available peptide precursors, making them accessible for a wide range of applications. These CPPs enter human cells as demonstrated by live-cell confocal microscopy using fluorescently labelled peptides. We report efficient sequences that demonstrate increased cellular uptake compared to conventional CPPs like the TAT peptide (derived from the transactivating transcriptional activator of human immunodeficiency virus 1) or octaarginine (R8), despite requiring only three positive charges. Bicyclization triggered by the presence of bismuth(III) increases cellular uptake by more than one order of magnitude. Through the analysis of cell lysates using inductive coupled plasma mass spectrometry (ICP-MS), we have introduced an alternative approach to examine the cellular uptake of CPPs. This has allowed us to confirm the presence of bismuth in cells after exposure to our CPPs. Mechanistic studies indicated an energy-dependent endocytic cellular uptake sensitive to inhibition by rottlerin, most likely involving macropinocytosis.